Influence of clove tea (Syzygium aromaticum) on body weight and biochemical parameters of rats subjected to ethanol consumption and abstinence - Mani, Fernanda [UNESP]; Braga, Camila Pereira [UNESP]; Novelli, Ethel Lourenzi Barbosa [UNESP]; Sforcin, José Maurício [UNESP] (OMICS International, 2012)
Clove has a large number of therapeutic properties and its tea has been used by the general population as antiinflammatory, antihyperglycemic, antimutagenic, bactericidal, and nematicidal, among others. Thus, the aim of this study was to assess the effect of clove on biochemical parameters of rats subjected to ethanol consumption and abstinence. The animals were subjected to ethanol intake before and after treatment with clove tea, according to their groups, as follows: GW received water (control); GE received 3% ethanol alone; GC received clove alone; GCE received clove for 7 consecutive days. Administration of clove tea or ethanol alone did not change serum parameters such as glucose, triglycerides, total cholesterol, total protein and albumin, and it did not alter weight gain although there was a significant difference in mean food consumption, which suggests that under such conditions clove tea or ethanol does not interfere with these parameters. On the other hand, administration of clove tea before or after ethanol administration led to significant changes in several parameters such as glucose, triglycerides, cholesterol, total protein and albumin. The obtained results thus suggest that prolonged ethanol intake should be avoided when clove tea is consumed daily.
Keywords: Clove; Ethanol; Glucose; Lipids; Proteins